A preliminary study on aquatic insect diversity and abundance in relation to fluctuating physiochemical parameters of an artificial pond - Sabina Noor,; Rafiq, Nosheen; Akbar, Palwasha; Zehri, Saima; Wali, Sana; Shahwani, Farzana (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
This preliminary study was conducted from April to October 2019, and hold the first account to outline the diversity of aquatic insects with influence to the fluctuating physiochemical parameters in the pond of Sardar Bahadur Khan Women’s University Quetta. The collection of 722 individuals in total presented four orders (Hemiptera, Ephemeroptera, Diptera and Odonata) and seven families. These individuals were labeled to generic level as Gerris sp., Notonecta sp., Anopheles sp., Thaumalae sp., Sympetrum sp., Orthetrum sp. and Heptagenia sp. Shannon-Weinner diversity and Simpson’s diversity index revealed greater values for backswimmers and mayflies (Notonecta and Heptagenia sp.). Additionally, Margalef’s richness index was also recorded highest (1.163) for backs-swimmers. Amongst physiochemical parameters, water temperature was ordinated in Gaussian’s species packing model. This ordination illustrated wider curve for Notonecta sp. and narrower curve for Anopheles sp., suggesting the maximum and minimum tolerance (temperature) range for these species in this specific pond community. Water pH of the pond also altered slightly and ranged from 9.13- 10.3 during April to August. As of the total dissolve solids (TDS), this study observed a raised from 253.16 mg/L to 432.11 mg/L till the end. Since aquatic insects play vigorous role in the stability of aquatic ecosystems, more relevant studies are required to be conducted to evaluate the broader range of these insects.